Digital Transformation through the Implementation of ERP (Enterprise Resource Planning) in Manufacturing Companies - Fahmi Ruziq; Dewi Wahyuni; M. Rhifky Wahyadi; Sattar Rasul (International Journal of Advanced Research, 2024)
The digital transformation of manufacturing companies has gained momentum, particularly through the implementation of Enterprise Resource Planning (ERP) systems. ERP systems are integrated software platforms that streamline core business functions, including finance, human resources, procurement, and production. These systems significantly improve operational efficiency, reduce costs, and enhance decision-making capabilities within manufacturing firms. The centralization of data and automation of routine tasks eliminate data silos and manual errors, leading to better coordination, real-time insights, and optimized resource allocation. However, ERP adoption comes with challenges, such as resistance to change, the complexity of system integration, and customization costs. Despite these hurdles, the long-term benefits, such as cost savings, improved collaboration, and enhanced customer relationship management, outweigh the initial investments. As ERP systems evolve with emerging technologies like artificial intelligence (AI) and the Internet of Things (IoT), they offer even more advanced capabilities in predictive maintenance, real-time monitoring, and automated decision-making. This paper concludes that ERP systems are crucial for the digital transformation of manufacturing companies, helping them become more agile, cost-efficient, and competitive in an increasingly digital world.